2003
DOI: 10.1093/bja/aeg236
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of desflurane administration in morbidly obese patients: a comparison with sevoflurane using an ‘inhalation bolus’ technique

Abstract: Immediate recovery was significantly faster in the desflurane group. Overall hypnotic controllability measured by BIS was less accurate with desflurane. Overall haemodynamic controllability was better when using desflurane. Fewer episodes of hypotension were found in the desflurane group. The use of the inhalation bolus was found to be appropriate in both groups without causing severe haemodynamic side effects. Minimal BIS values were significantly lower after a desflurane bolus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 25 publications
3
56
0
3
Order By: Relevance
“…Among these studies, De Baerdemaeker et al evaluated 50 obese patients and reported distinct outcome measurements in two studies. 3,15 In all trials, the recruited patients were American Society of Anesthesiologists (ASA) status I-III who underwent general anesthesia with endotracheal intubation. In addition, in all trials except one, the patients underwent elective bariatric operations; the one exception included obese patients who underwent intraabdominal, orthopedic, or other surgery.…”
Section: 13-22mentioning
confidence: 99%
See 2 more Smart Citations
“…Among these studies, De Baerdemaeker et al evaluated 50 obese patients and reported distinct outcome measurements in two studies. 3,15 In all trials, the recruited patients were American Society of Anesthesiologists (ASA) status I-III who underwent general anesthesia with endotracheal intubation. In addition, in all trials except one, the patients underwent elective bariatric operations; the one exception included obese patients who underwent intraabdominal, orthopedic, or other surgery.…”
Section: 13-22mentioning
confidence: 99%
“…In seven trials, desflurane was compared with sevoflurane for maintenance of anesthesia. 3,[13][14][15][16][17][18] Two studies compared the recovery profiles of patients given sevoflurane vs isoflurane for maintenance of anesthesia. 19,20 Another two studies compared the recovery parameters of patients given intravenous anesthesia with those given propofol and inhalational anesthesia.…”
Section: 13-22mentioning
confidence: 99%
See 1 more Smart Citation
“…At 1 LÁmin -1 , the average time to control the MAP was significantly shorter with desflurane [17 (12) min] than with isoflurane [29 (16) min], with 60% of the patients in the isoflurane group requiring rescue therapy. De Baerdemaeker et al 55 studied fifty morbidly obese patients undergoing laparoscopic gastroplasty who received BIS-guided sevoflurane or desflurane anesthesia in combination with a remifentanil target-controlled infusion. Intraoperative hemodynamic stability and BIS control were measured.…”
Section: Alveolar Ventilationmentioning
confidence: 99%
“…Returning the fresh gas to minimal flow but keeping the vaporizer setting about 25% greater than the previous setting is a bolus technique shown to improve stability and avoid overcorrection. 55 Likewise, reducing the anesthetic depth requires a major change in the vaporizer setting. A full closure of the vaporizer alone will lead to a slow decrease in Etaa; a bolus of fresh gas under observation of the Fiaa and Etaa is recommended if a more rapid reduction in anesthetic depth is required.…”
Section: Changing Anesthetic Depthmentioning
confidence: 99%